Gravitational Ultrafiltration Of River Water: Fouling And Cleaning Efficiency Study - Bachok @ Joffri, Luqman Hakim (Universiti Sains Malaysia, 2021)
Gravity Driven Ultrafiltration System is a promising technology which could produce potable water to the community with no electricity and proper wastewater treatment. This project focuses on the construction of the non-point source, modular type GDU system to filter the river water using the Krian river as source water. The GDU systems are tested under both depleting and constant hydrostatic pressure conditions. Under depleting hydrostatic pressure at 40 cm, the highest flux was found at 0.58 LMH and it reduce to almost zero due to reduction of hydrostatic pressure and exhaustion of river water in the module. The module can recover its flux up to 85.17% after being backwash for 5 cycles. Under constant hydrostatic pressure, it was found that 40 cm length hollow fibres produce the lowest permeation flux stabilization due to the larger extent of fouling. Therefore, the tendency for fouling is higher at longer membrane. This can be seen through the characterization of membrane using SEM and FTIR by comparing the pristine membrane with the fouled membrane. Water quality test using different parameters are used to determine the amount in the river water before and after undergoing GDU system. It was found out the concentration of parameters tested on the permeate water is lesser compared to the river water, especially on the bigger molecule. The quality of the permeate is safe for human activity according to the guideline outlined by WHO. The module can recover its flux up to 36.83,86.26 and 94.32% for 40,35 and 30 cm respectively after backwash for 5 cycles. The modular GDU system is promising to provide the clean water for the community that is deprived of electricity and water treatment facilities.